2020
DOI: 10.3390/polym13010022
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulating MoO2 Nanocrystals into Flexible Carbon Nanofibers via Electrospinning for High-Performance Lithium Storage

Abstract: Design and synthesis of flexible and self-supporting electrode materials in high-performance lithium storage is significant for applications in the field of smart wearable devices. Herein, flexible carbon nanofiber membranes with uniformly distributed molybdenum dioxide (MoO2) nanocrystals are fabricated by a needlefree electrospinning method combined with the subsequent carbonization process, which exhibits outstanding structural stability under abrasion and deformation. The as-fabricated lithium-ion batterie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…When, the Li/MoO2@C half cells cycled at 0.5 and 10 A g −1 retain 861 and 312 mAh g −1 capacity after 140 and 268 cycles, respectively. Recently, Zhang et al [515] reported the design and fabrication of a composite, which consists of encapsulated MoO2 nanocrystals into flexible carbon nanofibers, using a needle-free electrospinning method combined with the subsequent carbonization process. The MoO2/C nanofiber membrane as self-supporting anode exhibits a discharge capacity of 450 mAh g −1 after 500 cycles at 2000 mA g −1 .…”
Section: Moo2 Compositesmentioning
confidence: 99%
“…When, the Li/MoO2@C half cells cycled at 0.5 and 10 A g −1 retain 861 and 312 mAh g −1 capacity after 140 and 268 cycles, respectively. Recently, Zhang et al [515] reported the design and fabrication of a composite, which consists of encapsulated MoO2 nanocrystals into flexible carbon nanofibers, using a needle-free electrospinning method combined with the subsequent carbonization process. The MoO2/C nanofiber membrane as self-supporting anode exhibits a discharge capacity of 450 mAh g −1 after 500 cycles at 2000 mA g −1 .…”
Section: Moo2 Compositesmentioning
confidence: 99%
“…36,38 The C 1s XPS spectrum is displayed in Figure 1g, and it can be clearly seen that there are three peaks located at 284.6, 285.9, and 288.9 eV, which could be attributed to C� C, C−O, and C�O bonds, respectively. 39,40 The existence of carbon in the MoO 2 /Cu 2−x Se@C octahedron was further evidenced by Raman spectroscopy (Figure S5). There are two obvious characteristic peaks at 1371 and 1595 cm −1 , corresponding to the D peak and G peak of carbon, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…In addition, there is a weak peak at 943.0 eV in the middle of the two peaks, which indicates that the Cu element mainly exists in the valence state of Cu + . , In the high-resolution Mo 3d spectrum, the peaks are fitted into two parts (Figure e). Two characteristic peaks at 228.9 and 232.5 eV, respectively, belong to Mo 6+ (3d 3/2 ) and Mo 6+ (3d 5/2 ), , while other peaks at 232.1 and 235.8 eV correspond to Mo 4+ (3d 3/2 ) and Mo 4+ (3d 5/2 ), suggesting the surface oxidation of MoO 2 . As shown in Figure f, the high-resolution O 1s spectrum shows two obvious characteristic peaks at 530.9 and 532.2 eV, which are mainly attributed to Mo–O and C–O bonds, respectively. , The C 1s XPS spectrum is displayed in Figure g, and it can be clearly seen that there are three peaks located at 284.6, 285.9, and 288.9 eV, which could be attributed to CC, C–O, and CO bonds, respectively. , …”
Section: Resultsmentioning
confidence: 95%
“…Table 5 summarizes the electrochemical performance of various MoO 2 anode materials prepared by various synthetic processes [ 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 ]. The different strategies demonstrate the ability to mitigate the particle pulverization as a consequence of Li insertion/extraction and improve the MoO 2 electrochemical performance via the fabrication of nanocomposites including carbonaceous materials.…”
Section: Resultsmentioning
confidence: 99%